2004
DOI: 10.1507/endocrj.51.279
|View full text |Cite
|
Sign up to set email alerts
|

Lipoatrophic Diabetes in an Elderly Woman: Clinical Course and Serum Adipocytokine Concentrations

Abstract: Generalized lipodystrophy is a rare disorder of adipose tissue, whose etiology remains unknown. Pathophysiology of this disorder is characterized by generalized loss of body fat associated with an infrequent form of diabetes mellitus (lipoatrophic diabetes). Main features of this form of diabetes mellitus are the severe insulin resistance and the absence of ketoacidosis. Lipodystrophy can be congenital or acquired. In the acquired form, metabolic disturbances usually begin in the first years of life and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…TNF-α is of particular interest, having been closely linked to obesity and the metabolic syndrome [20]. In contrast to our data, Hegele et al [2] found no change in plasma TNF-α in FPLD, although a recent case report of an individual with acquired idiopathic generalised lipodystrophy reported elevated plasma TNF-α in the presence of reduced adiponectin and leptin levels [10]. The relationship between adiponectin and the TNF-α system is of particular interest.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…TNF-α is of particular interest, having been closely linked to obesity and the metabolic syndrome [20]. In contrast to our data, Hegele et al [2] found no change in plasma TNF-α in FPLD, although a recent case report of an individual with acquired idiopathic generalised lipodystrophy reported elevated plasma TNF-α in the presence of reduced adiponectin and leptin levels [10]. The relationship between adiponectin and the TNF-α system is of particular interest.…”
Section: Discussioncontrasting
confidence: 85%
“…Thus, the low-adiponectin state may be the common defect in both obesity and lipodystrophy. However, increased plasma levels of various proinflammatory cytokines expressed by adipose tissue have also been observed in various groups of lipodystrophic subjects [7][8][9][10][11]. The aim of the present study was to investigate the interrelationships between the abnormalities of adiponectin and other adipokines, and to determine which defects are most closely predictive of the metabolic syndrome in a genetically and phenotypically well-characterised group of subjects with FPLD and unaffected controls.…”
Section: Introductionmentioning
confidence: 96%
“…The plasma resistin is low in those patients, as reported by Iglesias and his colleagues [18], indicating that plasma resistin may not be related to the insulin resistance in patients with lipodystrophy. Tumor necrosis factor-α, a proinflammatory cytokine, also secreted from adipocytes, is reported to elevate plasma levels in a patient with AGL [18] and it is assumed that this might play a role in insulin resistance. The possible pathological mechanisms linking lipodystrophy and insulin resistance are summarized in Figure 2.…”
Section: Discussionmentioning
confidence: 56%
“…Serum leptin and adiponectin levels reflecting the amount of body fat are extremely low in patients with AGL and may be related to severe insulin resistance and its metabolic complications in lipodystrophies [11,13,30,31]. The plasma resistin is low in those patients, as reported by Iglesias and his colleagues [18], indicating that plasma resistin may not be related to the insulin resistance in patients with lipodystrophy. Tumor necrosis factor-α, a proinflammatory cytokine, also secreted from adipocytes, is reported to elevate plasma levels in a patient with AGL [18] and it is assumed that this might play a role in insulin resistance.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation